PENGARUH PROFITABILITAS, LEVERAGE DAN CORPORATE GOVERNANCE TERHADAP PERENCANAAN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017 - Rahmadini, Indah; Ariani, Nita Erika (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2019)
This study aims to examine the effect of profitability, leverage, and corporate governance on tax planning. The independent variables used in this study are profitability, leverage, institutional ownership, managerial ownership, independent commissioners and audit committees. While the dependent variable in this study is tax planning.Tax planning in this study the measured of Cash Effective Tax Rate (CETR). The population in this study are manufacturing companies listed on Indonesian Stock Exchange (BEI) in the period 2014-2017. Determination of samples in this study using purposive sampling method. There are 45 manufacturing companies listed on BEI used as research samples based on predetermined criteria. The results showed that profitability, leverage, managerial ownership, independent commissioners and audit committees had a significant effect on tax planning. Meanwhile institutional ownership has no significant effect on tax planning